Panorama of criminological reality and its future: on “Modern criminology as a science and academic discipline” by P.A. Kabanov, R.R. Magizov - G. N. Gorshenkov (Russian Journal of Economics and Law)
Objective: comprehensive and objective evaluation of a work by P. A. Kabanov and R. R. Magizov “Modern criminology as a science and educational discipline”, published in Kazan in 2017.Methods: dialectical approach to cognition of social phenomena using general scientific methods of cognition based on it:analysis, synthesis, comparison, etc.Results: the authors’ concept of modern criminology as a science and educational discipline is analyzed, as well as its structure, relationships with other sciences, main trends in criminology and prospects for its development. Much attention is paid to the unconditional usefulness of the publication, first of all, for those who study criminal law, because, as the authors rightly point out, modern criminological science is an extremely dynamic and multidimensional branch of knowledge, in respect of which a unified approach in understanding its main categories has not yet been developed.In the first chapter of P. A. Kabanov and R. R. Magizov’s work, the Russian image of criminology as a scientific branch and an educational discipline is presented. The second chapter describes the structure of modern criminology, which, according to the authors, was undergoing changes at the turn of the 1990s in the Russian model (theoretical and applied) of criminological science. Chapter 3 is devoted to the theory and practice of specific-sociological research as a universal method of criminological cognition and a form of teaching criminology. In the fourth chapter, the indisputable provisions on interrelations of modern criminology with social and natural sciences are systematized. The fifth chapter discusses trends and promising areas of criminology.The authors present critical estimations of some conventional views on criminology as a science with an ambiguous status that separates it from jurisprudence and, accordingly, draws it closer to sociology. The views of the reviewer on the status, structure, object, and function of criminology as a general theoretical, or normative, science are presented.Scientific novelty: for the first time, an assessment of the reviewed work is given, its main advantages and provisions requiring additional scientific study are revealed.Practical significance: the work determines the current state of Russian criminology and its prospects for conceptual development.